First‐line therapies for hepatitis B in the United States: A 3‐year prospective and multicenter real‐world study after approval of tenofovir alefenamide. Issue 8 (21st April 2022) - Pan, Calvin Q.; Afdhal, Nezam H.; Ankoma‐Sey, Victor; Bae, Ho; Curry, Michael P.; Dieterich, Douglas; Frazier, Lynn; Frick, Andrew; Hann, Hie‐Won; Kim, W. Ray; Kwo, Paul; Milligan, Scott; et al.
Abstract: Real‐world data are limited on tenofovir alafenamide (TAF). We aimed to study TAF real‐world outcomes with other first‐line regimens for chronic hepatitis B (CHB). We enrolled patients with CHB from 10 centers retrospectively and followed them for 36 months prospectively. We analyzed switching patterns of antiviral therapy and treatment outcomes of TAF, tenofovir disoproxil fumarate (TDF), and entecavir therapy. For efficacy and safety, we analyzed a subset of patients with complete data at 24 months after switching to TAF or remaining on TDF or entecavir. Among 1037 enrollees, 889 patients were analyzed. The mean age was 52%, and 72% were hepatitis B e antigen–negative. After enrollment, shifts in therapies were mostly in reduced use of TDF from 63% to 30% due to switching to TAF. Clinical parameters were compared at enrollment or initiation to measures at 24 months for patients remaining on TAF (187), TDF (229), or entecavir (181). At 24 months, a significantly higher portion of patients on TAF achieved hepatitis B virus (HBV) DNA ≤ 20 IU/ml (93% vs. 86%; p  = 0.012) and normalized alanine aminotransferase (ALT) (66% vs. 56%; p  = 0.031) with stable estimated glomerular filtration rates (eGFRs). However, a higher percentage of the patient with eGFR < 60 ml/mi/1.7 m 2 was observed in the TDF‐treated group (9% vs. 4%; p  = 0.010). In patients who remained on entecavir or TDF for 24 months, ALT and HBV‐DNA results did not differ significantly from baseline. Treatment of CHB in the United States has significantly shifted from TDF to TAF. Our data suggest that switching from TDF or entecavir to TAF may result in increased frequency of ALT normalization and potential clearance of viremia at the 24‐month time point. Abstract : Treatment of CHB in the US has significantly shifted from TDF to TAF. Our data suggest that switching from TDF or entecavir to TAF increased the frequency of ALT normalization and clearance of viremia.image